Carnap's conventionalism - Sungur, Uluğ R. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2006., 2006)
In this thesis Carnap's conventionalism is analysed. Carnap's distinction between internal questions of existence and external questions of existence, is the departure point of the analysis. However, it is claimed that we should not confine internal/external distinction with questions of existence. Following chapters deal with some main issues of Carnap's philosophy such as elimination of pseudo-problems of philosophy, ontological committment, rationality of scientific theory choice, scientific progress and the relations between linguistic frameworks and scientific theories. Finally, I suggest the concept of "intentional" rationality as a key concept for understanding Carnap's conventional and pragmatist approach beter.